Dades sobre el clergat urgellès que introduí la litúrgia catalanonarbonesa al bisbat de Palència en el segle XI - Ordeig i Mata, Ramon (Miscel·lània litúrgica catalana, 2012)
The documentation presented in this article confirms the thesis of Juan Pablo Rubio Sadia on the catalan origin of the clergy that introduced the Roman rite in the cathedral of Palencia in the occasion of its restauration in 1034. Apart from the essential role in this matter of the bishop Ponç of Oviedo, ancient abbot of Tavèrnoles, one can guess in addition the intervention of saint Ermengol, bishop of Urgell. A great-nephew of him, a member of the viscountal house of Conflent, died in Palencia in 1071 and made a legacy to the clergy of saint Antolín, that is, those of the Palentine cathedral. A bishop and an archdeacon of Palencia are acting in the diocese of Urgell between 1076 and 1090. These are some data, among others, that show the historical context in which the exceptional phenomenon of the penetration of the Catalan-Narbonese Liturgy in the diocese of Palencia came to be.